The role of erythrocyte indices and red cell distribution width (RDW) as predictors of iron deficiency anemia in children with acyanotic congenital heart disease - Hirli Septiana Sari; Herlina Dimiati; Anidar .Anidar; Nora Sovira; Heru Noviat Herdata; Eka Destianti Edward (AcTion: Aceh Nutrition Journal, 2026)
Congenital heart disease (CHD) affects 9.5 per 1,000 live births worldwide, with Asia showing the highest numbers. Erythrocyte indices such as MCV, MCH, MCHC, and RDW help screen for IDA. This study evaluated erythrocyte indices and RDW as predictors of IDA in pediatric patients. Fifty children aged 1 month to 18 years with acyanotic CHD participated in the study at Dr. Zainoel Abidin Hospital, Banda Aceh, from May to August 2025. IDA diagnosis required age-specific low hemoglobin plus two of the following: ferritin <12 ng/mL, serum iron <50 μg/dL, or TIBC >350 μg/dL. The results showed that 26% of the patients had IDA. The IDA group demonstrated low MCV (84.6%; p=0.001), MCH (53.8%; p=0.001), MCHC (38.5%; p=0.003), and high RDW (76.9%; p=0.001). Logistic regression revealed that low MCV (OR 17.109; 95% CI 2.392–122.397) and high RDW (OR 15.256; 95% CI 2.297–101.320) were the strongest predictors. In conclusion, these parameters effectively predicted IDA in children with cyanotic CHD. Low MCV was the most significant predictor, followed by elevated RDW.